The Impact of Sauna Bathing on Cardiovascular Homeostasis: From Molecular Mechanism to Clinical Benefits - Matusiak, Filip; Brzoza, Klaudia (Quality in Sport, 2026)
Background. Cardiovascular diseases (CVD) reamin the leading cause od death wordwilde, thereby demanding noveland scalable preventive approaches. In recent years, sauna bathing and infrared Waon therapy have emerged as potentialpleiotropic intervention replicating the effects of aerobic training. Aim. This review aims to summarize the evidence currently available from large prospective cohort studies and from randomized controlled trials on the influence of short-term thermal stress on hemodynamic parameters, endothelial function, arterial stiffness and long-term cardiovascular prognosis. Results. Observational studies strongly indicate that dose-dependent sudden cardiac death (63% reduction), stroke (61%), and hypertension are low in the frequent sauna users (4-7 times per week). These effects are mediated through upregulation of heat shock proteins (HSPs) modulation of the autonomic nervous system, and suppression of systemic inflammation. However, the results of studies testing these advanced exercise training strategies in patients with established CAD are conflicting regarding potential improvement in vascular function compared to healthy subjects, potentially resulting from a "healthy user" bias or structural limitations when disease is severe. Conclusions. Acute heat treatment may serve as a hormetic stressor that triggers beneficial pleiotropic adaptations. While the epidemiological evidence on risk reduction is strong for modification of these potentially reversible factors, the failure to demonstrate vascular benefit in short-term trial of advanced CAD patients demands additional investigation into the optimal approach regarding patient population, timing and duration of therapy.